Tackling increased risks in older adults with intellectual disability and epilepsy: Data from a national multicentre cohort study. (October 2022) - Watkins, L.V.; Henley, W.; Sun, J.J.; Perera, B.; Angus-Leppan, H.; Sawhney, I.; Purandare, K.; Eyeoyibo, M.; Scheepers, M.; Lines, G.; Winterhalder, R.; Shankar, R.
Highlights: People with intellectual disabilities (PwID) & epilepsy have poor clinical outcomes. Health profiles of PwID ≥40 years are comparable to general population ≥ 65 years. Clinical features & risk factors in older PwID (≥40 years) & epilepsy is unexplored. This study compares older PwID (n=405) & epilepsy with their younger peers (n=499). Older PwID had significantly higher co-morbidity, polypharmacy & epilepsy risks. Abstract: Purpose: People with intellectual disabilities (ID) suffer multimorbidity, polypharmacy and excess mortality at a younger age than general population. Those with ID and epilepsy are at higher risk of worse clinical outcomes than their peers without epilepsy. In the ID population the health profile of those aged ≥40 years can be compared to those aged over 65 in the general population. To date there is limited data available to identify clinical characteristics and risk factors in older adults (≥40 years) with ID and epilepsy. Methods: The Epilepsy in ID National Audit (Epi-IDNA) identified 904 patients with ID and epilepsy from 10 sites in England and Wales. This subsequent analysis of the Epi-IDNA cohort compared the 405 adults over 40 years with 499 adults ≥18 years aged under 40 years. Comparison was made between clinical characteristics and established risk factors using the Sudden Unexpected Death in Epilepsy (SUDEP) and Seizure Safety Checklist. Results: The older adults' cohort had significantly higher levels of co-morbid physical health conditions, mental health conditions, anti-seizure medications (median 5), and antipsychotics compared to the younger cohort. The older group were significantly less likely to be diagnosed with a co-morbid neurodevelopmental disorder, and to have an epilepsy care plan. Conclusion: This is the largest study to date focused on adults with ID and epilepsy over 40 years. The ≥40 years cohort compared to the younger group has higher levels of clinical risk factors associated with multi-morbidity, potential iatrogenic harm and premature mortality with worse clinical oversight mechanisms.